2006
DOI: 10.1093/ndt/gfl218
|View full text |Cite
|
Sign up to set email alerts
|

The influence of socio-demographic factors, treatment perceptions and attitudes to living donation on willingness to consider living kidney donor among kidney transplant candidates

Abstract: Background. Living donor, compared with cadaveric donor kidney transplantation, is associated with prolonged graft survival and increased life expectancy for patients with end-stage renal disease (ESRD). However, access to living donor transplantation remains variable. Our objective was to further our understanding of the factors associated with the willingness to consider living donor kidney transplant (LDKTx). Methods. All patients from two tertiary care hospitals being assessed for a LDKTx (n ¼ 81), and a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
61
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 13 publications
5
61
0
Order By: Relevance
“…One possible explanation is that older candidates are unwilling to ask young donors because of an appreciation that young donors have a long life expectancy during which they might develop medical problems that could be complicated by prior nephrectomy. Our observation corroborates that of Zimmerman et al, who studied transplant candidates undergoing evaluation and patients wait-listed for a deceased donor kidney and found that older age was associated with a lesser willingness to consider live donor transplantation (34).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One possible explanation is that older candidates are unwilling to ask young donors because of an appreciation that young donors have a long life expectancy during which they might develop medical problems that could be complicated by prior nephrectomy. Our observation corroborates that of Zimmerman et al, who studied transplant candidates undergoing evaluation and patients wait-listed for a deceased donor kidney and found that older age was associated with a lesser willingness to consider live donor transplantation (34).…”
Section: Discussionsupporting
confidence: 92%
“…Minimal published literature exists on how transplant candidates interact with donors. Although some transplant candidates seek altruistic donors through the media, the majority of donors are recruited through the personal relationships that comprise a candidate's social support network (14,17,34,35). Because these interactions are usually private, transplant professionals interested in donor recruitment need to rely on the self-report of candidates and donors to identify possible methods to increase live donation overall.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties in communication and interaction might result in difficulties in accessing health-care information, decreased demand for appropriate treatment options, and false information about transplantation and its risks that may result in building or reinforcing fears, worries and negative attitudes [35][36][37][38]. Furthermore, language barriers and marginal literacy may also form a barrier towards clarifying complex and difficult processes and may also build barriers to discussing complex or sensitive issues.…”
Section: Patient Preferences and Decision-making Towards Renal Transpmentioning
confidence: 99%
“…Although living donor transplantation remains an underutilized modality, there has been relatively little research exploring factors associated with potential reservations about and with barriers to living donor transplants both in health-care professionals and in patients and family members [37]. Cadaveric kidney donation rates are substantially lower for racial and ethnic minorities compared with white patients.…”
Section: Patient Preferences and Decision-making Towards Renal Transpmentioning
confidence: 99%
“…Previous studies of KTR have focused on the effects that specific, and largely singular, factors play in living or deceased transplant rates. These have included the effects on transplantation rates of religion 6,7 , probabilities of need 8 , demographic factors and attitudes 9 , marital status 10 , gender 11 , geographic variation 12 , presumed consent policies 13 and socioeconomic status 13 . While these studies have provided valuable insight into the potential for single locus variables to influence rates of renal transplantation, few have focused upon more than one country, and, while one 13 has focused on several of the variables included in our study, none has attempted to associate the relationships of so many different factors for both living and deceased KTR during a specific, homogeneous time frame, across such a large number of countries.…”
mentioning
confidence: 99%